The Juridical Analysis of Judges' Consideration of Working Age Discrimination based on the 1945 Constitution and Legislation (Study of Constitutional Court Decision Number 35 / PUU-XXII / 2024) - Saputri, Audi Febriella Dion; Nailul Author, Ahmad (Universitas Negeri Surabaya, 2025)
The emergence of Decision MK Number 35/PUU-XXII/2024 is a response to a conflict related to discrimination in working age requirements in Indonesia. This conflict stems from the conflict between the company's freedom to determine the conditions for recruiting workers, which is regulated in Article 35 Paragraph (1) of the Manpower Law, and workers' rights, which are regulated in Article 28D Paragraph (2) of the 1945 Constitution. This issue is raised because the age limit applied by companies not only limits access to employment, but also violates the principles of non-discrimination and social justice which have been regulated by Pancasila and the 1945 Constitution. The type of research chosen in this research is normative legal research. This type of normative legal research was chosen for this research because there is a blurring of norms in the judge's consideration and the judge's verdict in Decision MK Number 35/PUU-XXII/2024, namely that there is a conflict with Article 28D Paragraph 2 of the 1945 Constitution. However, unfortunately the verdict stated that the judge rejected the applicant's petition in its entirety. But there is also a dissenting opinion by one of the judges which can be a supporting material. Therefore, this research is expected to provide recommendations on the possibility of further legal remedies, such as a review of Article 35 Paragraph 1 of the Labor Law, to ensure that labor regulations in Indonesia do not conflict with the constitutional rights of citizens. Keywords : Judges Consideration, Discrimination, Working Age Requirement, Dissenting Opinion